ANALISIS PRODUKTIVITAS SEBAGAI SALAH SATU INDIKATOR KESEHATAN HUTAN (Studi Kasus Pada Hutan Rakyat Jati di Kecamatan Natar Kabupaten Lampung Selatan Provinsi Lampung) - Siti Fauzia Rochmah; Afif Bintoro; Hari Kaskoyo; Rahmat Safe'i (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
Currently, community forests are increasingly showing an important role in meeting the timber demand for the timber industry. This can be seen from the log production which continues to decline every year. The reduced supply of wood from natural and plantation forests is one of the reasons why community forests are used as an alternative to meet the demand for industrial wood raw materials. This study aims to determine the parameter value of productivity indicators and health status of jati community forests in Natar District. To achieve this, the stages include: determining the number of plot calculators, making FHM plot clusters in teak community forests, collecting data and analyzing productivity data and the final forest health value. The results of this study indicate that jati community forests in Natar District, South Lampung Regency have good forest health values ​​based on productivity indicators. This will affect the management of community forests in the future with the main function of forests, namely production. By knowing the productivity value and health condition of the forest, managers can make appropriate forest management decisions.